Hamstring strain injuries: Incidence, mechanisms, risk factors, and training recommendations. - Wing, C.; Bishop, C. (Strength and Conditioning Journal, 2020)
Hamstring strain injury (HSI) is one of the most commonly reported sports injuries. This has led to a substantial amount of research aimed at identifying factors that increase the risk of an athlete suffering a HSI. The identification of risk factors allows practitioners to plan intervention programs with the aim of reducing the rate and severity of HSI. As a multitude of factors contribute to the risk of HSI, interventions should be multifaceted in nature. This review outlines the incidence, mechanisms, and risk factors for HSI and provides evidence-based training recommendations to reduce the rate and severity of HSI.